2019
DOI: 10.1007/s13384-019-00302-w
|View full text |Cite|
|
Sign up to set email alerts
|

“Portray cultures other than ours”: How children’s literature is being used to support the diversity goals of the Australian Early Years Learning Framework

Abstract: Catering for diversity within birth to 5-year-old settings continues to be an on-going concern for policy makers and educators worldwide. This research contributes to discussion on the value of children’s literature in achieving international principles of diversity and, in particular, the Principles, Practice and Outcomes outlined in the Australian Early Years Learning Framework. The article considers the selection and use of children’s literature related to diversity, as well as what influences these process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 21 publications
4
15
0
1
Order By: Relevance
“…In accordance with the aforementioned authors, Adam et al (2019) find that books are a method for highlighting diversity within a group of children. However, this demands that ECEC teachers have specific skills and a broad knowledge of the issues under discussion.…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…In accordance with the aforementioned authors, Adam et al (2019) find that books are a method for highlighting diversity within a group of children. However, this demands that ECEC teachers have specific skills and a broad knowledge of the issues under discussion.…”
Section: Resultssupporting
confidence: 79%
“…Leibowits et al further indicate that this is an impactful activitythey spoke to teenagers who had participated in the activity as children, who indicated that they had learned a lot about their peers from this experience. In accordance with the aforementioned authors, Adam et al (2019) find that books are a method for highlighting diversity within a group of children. However, this demands that ECEC teachers have specific skills and a broad knowledge of the issues under discussion.…”
Section: Cultural Diversitysupporting
confidence: 79%
See 1 more Smart Citation
“…As with the pilot study (Adam et al 2017(Adam et al , 2019, the majority of the characters or people of colour in the books with some representation of diversity had secondary roles with the main characters being Caucasian. In many of the books, these characters played no part in the text of the story, only being present in pictures as background characters.…”
Section: Limited Perspectivesmentioning
confidence: 98%
“…Evidence also highlights the importance of including literature as a way of introducing children to others who are different from themselves (Bishop 1992(Bishop , 1997(Bishop , 2012Boutte et al 2008;Klefstad and Martinez 2013;Sims 1982;Souto-Manning et al 2018). However, evidence suggests that many childhood education and care centres in English-speaking countries, including Australia, provide monocultural, exclusive and potentially biased literature that can cumulatively impact on children's long term attitudes and perceptions of diversity and well-being (Adam et al 2017(Adam et al , 2019Boutte et al 2008;Stallworth 2006;Souto-Manning et al 2018).…”
Section: Introductionmentioning
confidence: 99%